2002
DOI: 10.4067/s0718-19572002000200002
|View full text |Cite
|
Sign up to set email alerts
|

Desarrollo embrionario y larval del bolo Diplectrum radiale Quoy y Gaimard, 1824 (Pisces: Serranidae)

Abstract: Self-fecundation of Diplectrum radiale a synchronic hermaphrodite species, was induced through a manual process; the fertilization percentage was 86.92 ± 2.75%, producing spherical, floating eggs, with a centric oil drop, a reduced perivitelline space and a smooth envelop. Fertilized eggs had an average diameter of 0.67 ± 0.02 mm and a oil drop with an average diameter of 0.13 ± 0.01 mm at 26.41 ± 0.25°C, pH 8.84 ± 0.17 and 38 ± 1 ppm of salinity. The embryonic development was described, observing the first cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
1
1
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 3 publications
(7 reference statements)
1
1
1
2
Order By: Relevance
“…The pharyngula stage included the formation of structures such us optical capsules, Kupffer vesicle and somites, and the appearance of melanophores for pigmentation. All of these structures were observed for Peruvian grunt and matched with those described for D. radiale (López et al 2002) The incubation time for of Peruvian grunt was 31-40 h at specific temperature of 19°C, this time is specie-specific and several authors documented that the temperature is one of the main environmental factors that influence the time and percentage of hatching in marine fish (Bobe & Labbé 2010). In some species, this influence was observed for example spotted rose snapper L. guttatus were 15 h at 26.3-28.2 ºC (Boza-Abarca et al 2008) and 21 h at 25-26 °C (Alvarez-Lajonchère et al 2012), for Pacific red snapper L. peru were 23, 20 and 18 h at 26, 28 and 30 °C, respectively.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…The pharyngula stage included the formation of structures such us optical capsules, Kupffer vesicle and somites, and the appearance of melanophores for pigmentation. All of these structures were observed for Peruvian grunt and matched with those described for D. radiale (López et al 2002) The incubation time for of Peruvian grunt was 31-40 h at specific temperature of 19°C, this time is specie-specific and several authors documented that the temperature is one of the main environmental factors that influence the time and percentage of hatching in marine fish (Bobe & Labbé 2010). In some species, this influence was observed for example spotted rose snapper L. guttatus were 15 h at 26.3-28.2 ºC (Boza-Abarca et al 2008) and 21 h at 25-26 °C (Alvarez-Lajonchère et al 2012), for Pacific red snapper L. peru were 23, 20 and 18 h at 26, 28 and 30 °C, respectively.…”
Section: Discussionsupporting
confidence: 72%
“…However, it was smaller than those reported for black grunt Haemulon bonariense 0.20 ± 0.02 mm (Cuartas et al 2003) and red porgy Pagrus pagrus 0.18-0.20 mm (Machinandiarena et al 2003). In relation to Peruvian grunt newly hatched larvae (2.558 ± 0.051 mm) there were larger than those reported for pond perch Diplectrum radiale 1.33 ± 0.02 mm (López et al 2002), H. bonariense 1.42 + 0.05 mm (Cuartas et al 2003) and colorado snapper Lutjanus colorado 1.9 mm of length (Abdo-de la Parra et al 2014). There are some studies about the size of hatched larvae in which it had been observed a positive correlation between larval size length and egg size, for example Acipense baeri and Acanthopagrus schlegeli (Gisbert et al 2000, Kang et al 2014.…”
Section: Discussionmentioning
confidence: 59%
“…The egg diameter of European sea bass Dicentrarchus labrax were 1.162±0.004 mm (Saka et al, 2001) and gilthead sea bream Sparus aurata were 1.001±0.005 mm (Kamacı et al, 2005) which is similar with the present study (1.1-1.3 mm). In relation to P. hasta newly hatched larvae (1.6-1.8 mm) there were slightly larger than those reported for pond perch Diplectrum radiale 1.33±0.02 mm (López et al, 2002), H. bonariense 1.42 + 0.05 mm (Cuartas et al, 2003) and somewhat smaller than colorado snapper Lutjanus colorado 1.9 mm of length (Abdode la Parra et al, 2014). Newly hatched larvae (1.5-1.7 mm) of S. argus fish in the same order was concomitant with the present study (Su et al, 2019).…”
Section: Embryonic Developmentcontrasting
confidence: 57%
“…Sprague et al (2001), López et al (2002) afirman que las divisiones consecutivas de los blastómeros no están separadas por períodos de crecimiento y los blastómeros resultantes tienen sólo la mitad del tamaño original después de cada división. Durante el proceso de desarrollo se observó la vesícula de Kupffer.…”
Section: Discussionunclassified
“…López et al (2002) refieren un tiempo de eclosión de 17: 23 horas a 27ºC para Diplectrum radiale, Cuartas et al (2002) afirma que el tiempo de eclosión para Haemulom bonariense fue de 15:19 horas a 27ºC. Todas las especies mencionadas anteriormente al igual que la especie estudiada, son tropicales y en ninguno de estos casos los huevos sobrepasaron los 0.8 mm de diámetro.…”
Section: Discussionunclassified